A Comparison Between Video Tape and Live Demonstration Methods for Teaching of Fissure Sealant Placement Procedures for Dental Students of Zahedan University of Medical Sciences in 2010-2011 - Alireza Ansari Moghadam; Fateme Arbabi Kalati; Mahkame Mirkarimi (Tehran University of Medical Sciences, 2012)
Background and Aims: Teaching of clinical skills is one of the most important aspects in training medical students. The aim of this study was to compare the effectiveness of videotaped and live demonstrations for applying fissure sealant on permanent molar teeth at Zahedan University of Medical Sciences (2010-2011).Materials and Methods: Thirty 8th-semester dental students were randomly assigned in two groups (n = 15). In group 1, fissure sealant placement was taught using live demonstration; while, in group 2, education was performed by videotaped demonstration. Then, each student applied fissure sealant on the patient's permanent molar tooth. The procedure of fissure sealant placement was assessed and scored by a pedodontist. The students were subsequently asked to rate how helpful the videotape or live demonstration had been. The data were analyzed using T-test and Chi-square test.Results: The mean students' scores for videotaped and live demonstration were 16.5 and 16.53, respectively. There was no significant difference between the teaching methods according to students' scores (P>0.05). 33% of students rated videotaped demonstration as "good" for its helpfulness and 66% as "very good". However, live demonstration was rated as "good" and "very good" by 66% and 33% of students, respectively. There was no significant difference between two groups (P>0.05).Conclusion: Both teaching methods were equally effective. Therefore, videotaped demonstration can be used in combination with live demonstration or as an alternative for it.